Peran Kepercayaan dalam Memediasi Pengaruh Influencer Endorsement dan Ulasan Pelanggan Online terhadap Niat Beli pada Produk Skincare Npure - Ulfatul Mukarromah; Edy Purwo Saputro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this research is to evaluate the impact of influencer endorsements, online customer reviews, purchase intention, and trust levels. The research adopts a quantitative approach. Data was collected through questionnaires, with respondents' responses measured using a five-point Likert scale. Data analysis was conducted using Smart-PLS version 3.0 software. The analysis results indicate that trust is significantly and positively influenced by influencer endorsements and online customer reviews. Trust significantly and positively affects purchase intention. However, influencer endorsements have no effect on purchase intention. Conversely, online customer reviews have a significant positive effect on purchase intention. Furthermore, influencer endorsements and online customer reviews significantly influence purchase intention through the role of trust.